bahasa inggris - Muhammad Samson Fajar; Enizar; Abdul Qodir Zaelani; Sofyan Munawar (Universitas Darunnajah Jakarta, Indonesia, 2025)
The increasing phenomenon of individuals choosing to be single in the modern era is a significant social change. Various factors such as career busyness, individual freedom, and changes in social values ​​have influenced people's mindsets towards the institution of marriage. This study analyzes how the critical reasoning of the Qur'an responds to the phenomenon of being single with a multidisciplinary approach that combines the historical reasoning of Muhammad Arkoun, the epistemology of Al-Ghazali, and the fiqh of ikhtilaf of Ibn Rushd. The research method used is library research, by making the Qur'an as the main source in responding to the law of celibacy (rahbaniyah). Secondary data was obtained from relevant books of interpretation, history, sociology, and psychology. The results of the study show that although Islam does not absolutely prohibit individuals from being single, marriage remains an institution recommended in Islam to maintain social stability and the sustainability of civilization. In the dialectical analysis, it was found that Arkoun emphasized the historical and social context in understanding Islamic teachings, while Al-Ghazali saw the spiritual and moral aspects of the individual in the decision to be single. Ibn Rushd, with his ikhtilaf fiqh approach, emphasized that marriage has flexible laws depending on the individual and social conditions. Therefore, this study concludes that marriage is more recommended than being single because it has broader benefits in social, economic, and psychological aspects, although it still provides space for individuals to consider their personal conditions.